2000
DOI: 10.1046/j.1440-1681.2000.03282.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects Of NKH477 On Endothelin‐1‐Induced Renal Responses In Anaesthetized Dogs

Abstract: 1. Intrarenal arterial infusion of a direct adenylate cyclase activator (NKH477; 300 ng/kg per min) increased renal blood flow, urine flow rate and urinary sodium excretion in anaesthetized dogs. 2. Intrarenal arterial infusion of endothelin (ET)-1 (2 ng/kg per min) reduced basal values of these parameters and glomerular filtration rate, which were recovered by the addition of NKH477 during ET-1 infusion. 3. These results demonstrate that NKH477 can counteract ET-1-induced antinatriuresis, mainly by restoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2003
2003
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(14 reference statements)
1
2
0
Order By: Relevance
“…CDH (0.25 µg/kg/min) increased the RBF significantly without reducing the BP, but higher doses of CDH had little effect on the RBF. Intrarenal arterial infusion of CDH (300 ng/kg/min) increased the RBF in anesthetized dogs [5, 6]. Although we administered CDH intravenously, our results are consistent with these findings.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…CDH (0.25 µg/kg/min) increased the RBF significantly without reducing the BP, but higher doses of CDH had little effect on the RBF. Intrarenal arterial infusion of CDH (300 ng/kg/min) increased the RBF in anesthetized dogs [5, 6]. Although we administered CDH intravenously, our results are consistent with these findings.…”
Section: Discussionsupporting
confidence: 87%
“…It acts directly on adenylate cyclase to increase intracellular cyclic adenosine monophosphate (cAMP) levels [4], with positive inotropic effects and lowering of the blood pressure (BP) [1]. Several investigators have shown that intrarenal arterial infusion of CDH increases the renal blood flow (RBF) in anesthetized dogs [5, 6]. More recently, Ogata et al [7]reported that CDH is capable of maintaining the urine volume, suggesting that CDH improves BP and RBF by maintaining the RBF in patients with heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, much attention has been paid to the effects of CDH on renal function, and several investigators have reported that CDH increases renal blood flow in anesthetized dogs [8][9][10]. Ogata et al [11] reported that CDH maintains urine volume, which suggests that CDH improves blood pressure and renal blood flow (RBF) in patients with heart failure, and that CDH could be used to maintain RBF clinically.…”
Section: Introductionmentioning
confidence: 99%